Accuracy of serum procalcitonin, C-reactive protein, and soluble CD14 subtype levels in diagnosis of sepsis in children - Knežević Rangelov, Sanja; Janković, Slobodan M. (Vojnosanitetski pregled, 2021)
Background/Aim. Despite the widespread use of procalcitonin, C-reactive protein (CRP), and soluble CD14 subtype (sCD14-ST), their diagnostic accuracy in children with sepsis is not yet clear. The aim of the study was to establish and compare the diagnostic accuracy of procalcitonin, CRP, and sCD14-ST in children admitted to the hospital under suspicion of having sepsis. Methods. The study was designed as a retrospective cross-sectional study on children admitted to the Pediatrics Clinic in Kragujevac, Serbia, under suspicion of sepsis, during a 6-month period. Diagnostic accuracy was tested by the construction of receiver operating characteristic (ROC) curves and their comparison in terms of area under the curve (AUC). Results. Procalcitonin had the largest AUC [0.75; 95% confidence interval (CI) 0.63–0.88], followed by CRP (0.68; 95% CI 0.54–0.81) and sCD14-ST (0.65; 95% CI 0.52 – 0.79). Differences between the areas under the ROC curves were not significant (CRP vs. procalcitonin z = 1.054, p = 0.291; CRP vs. sCD14-ST z = 0.238, p = 0.812; procalcitonin vs. sCD14-ST z = 1.089, p = 0.286). Conclusion. Our study showed relatively low sensitivity and moderate specificity of procalcitonin, C-reactive protein and sCD14-ST in diagnosing sepsis among children, as well as similar diagnostic accuracy of the three biomarkers.